2003
DOI: 10.7326/0003-4819-139-2-200307150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Angiotensin-Converting Enzyme Inhibitor on Residual Renal Function in Patients Receiving Peritoneal Dialysis

Abstract: Although the trial was small and had a limited ability to exclude effects of potential confounding factors, the angiotensin-converting enzyme inhibitor ramipril may reduce the rate of decline of residual renal function in patients with end-stage renal failure treated with peritoneal dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
5
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(193 citation statements)
references
References 29 publications
10
176
5
2
Order By: Relevance
“…Efforts to preserve residual renal function are likely to be beneficial for both MHD and PD patients. Randomized, controlled trials have demonstrated that angiotensin-converting enzyme inhibitors or angiotensin receptor blockers are renoprotective among PD patients (93,94). Even though there is no evidence that slowing the rate of decline of residual renal function translates into a survival benefit for maintenance dialysis patients, a controlled trial to test this hypothesis is probably unethical.…”
Section: Focus On the Future: Efforts To Continue To Improve Outcomesmentioning
confidence: 99%
“…Efforts to preserve residual renal function are likely to be beneficial for both MHD and PD patients. Randomized, controlled trials have demonstrated that angiotensin-converting enzyme inhibitors or angiotensin receptor blockers are renoprotective among PD patients (93,94). Even though there is no evidence that slowing the rate of decline of residual renal function translates into a survival benefit for maintenance dialysis patients, a controlled trial to test this hypothesis is probably unethical.…”
Section: Focus On the Future: Efforts To Continue To Improve Outcomesmentioning
confidence: 99%
“…However, furosemide has been used successfully to achieve diuresis and improved fluid balance, without influencing residual renal function [44]. The use of angiotensin-converting enzyme inhibitors (ACEi) and angiotensin II receptor blockers in adult PD patients suggests a positive effect on preserving residual renal function [45,46]. Results of the Effect of Strict Blood Pressure Control and ACE Inhibition on Progression of CRF in Pediatric Patients (ESCAPE) trial evaluating the effect of ramipril on estimated glomerular filtration rate (eGFR) and proteinuria in children with CKD, including a small cohort of PD patients, are awaited.…”
Section: Residual Renal Functionmentioning
confidence: 99%
“…b) Prevention of hypotensive episodes c) Use of an angiotensin-converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARBs) reduces the rate of decline in RRF and possibly delays the development of complete anuria in patients performing PD 40,41 .…”
Section: Protection Of Rrfmentioning
confidence: 99%